ANALISIS KEEFEKTIFAN SISWA SEKOLAH MENENGAH BELAJAR DI RUMAH - Febriyani, Erni; Purnamasari, Ratih; Sobari, Teti (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2018)
Research and analysis conducted by the author this time talking about the "effectiveness of students Learning At Home".  In the era of technological developments such as today's students are required to be able to divide their time between learning by playing gadgetnya. It is intended that students can compete with thousands of other students who are in Indonesia and even in foreign countries. This study aims to determine the suitability of the theory of the effectiveness of student learning at home with the facts that occurred in the field. This research included in this type of research to find out information as well as the alignment of the theory which refers to the expert opinion in the field. objects in this study were students from two different educational levels in order to create sustainable results with theory and that happens on the field. The objects of this study are that the authors take some students from two different levels of education is high school education level xl class either sains or social and the junior high school level VII class or class VIII.